The role of basic needs and attachment styles in prediction the life satisfaction of the high school students - Ali Karimi; Hossein Karsazi; Alireza Fazeli Mehrabadi; Ghasem Abdolpour (روانشناسی و روانپزشکی شناخت, 2021)
Introduction: Life satisfaction is an essential component of students' psychological health. Therefore, identifying the factors influencing students' life satisfaction is very important. Aim: The aim of this study was to investigate the role of basic needs and attachment styles in predicting life satisfaction of high school students. Method: The design of the present study was descriptive-correlational. The statistical population of this study includes all high school students during the academic year of 2016-2017. 459 students (299 boys and 160 girls) of the second-grade secondary school of District 2 of Qom were selected as the sample by convenience sampling. The instruments used included the Basic Psychological Needs Scales (PBNS), Attachment Styles Scale, and Satisfaction with Life Scale (SWLS). Pearson correlation coefficient and regression analysis were used to analyze the data. Results: The results of regression analysis showed that autonomy and competence with standard coefficient 0.21 (p<0.01) and 0.31(p<0.01) respectively, and secure and ambivalent attachment styles with standard coefficients 0.12 (p<0.05) and – 0.31 (p<0.01) respectively, have an effect on life satisfaction of students. The basic need for Relatedness and the Avoidant attachment style were not able to predict the life satisfaction. Conclusion: The results of this study confirmed the role of basic psychological needs and attachment styles in predicting the life satisfaction of high school students. Therefore, it is necessary to pay attention to the role of factors of basic psychological needs and attachment styles in improve the life satisfaction of students.